WATER QUALITY STATUS AT INTEGRITY AREA OF BUNGUS OCEAN FISHING PORT BASED ON WATER CLASSIFICATION - Herdiana Mutmainah; Ilham Adnan (AQUASAINS, 2017)
Ocean Fishing Port Bungus Complex is an integrated area in ocean fishing port that bordered by the sea (Mentawai Strait), traversed by a small river and surrounding by paddy fields. There are several facilities in PPS Bungus Complex such as fishing port, waters surveillance, research, fishery processing industry, settlement and others. Various activities that exist certainly have an impact to the existing waters. The purpose of this research is to know the status of water quality based on water classification. The result of analysis based on Government Regulation No.82 Year 2001 which conducted on water classifiction at estuary and outlet shows that the condition of waters is including to the Class IV for agriculture and industry, while around wharf, waters including to the Class III, for fishery. The water index classifiction based on Living Environment Minister Decree No.115 Year 2003 shows that estuary, outlets and wharf are not polluted. Result of analysis to waters for Class IV showed index 0,780 at estuary and 0,712 at outlet, while at wharf showed index 0,794 or Class III. Some parameters such as turbidity, BOD and Cd in estuary and outlet slightly exceeded the quality standard but are still within tolerable limits (Living Environment Minister Decree No.51 Year 2004). Based on the Living Environment Minister Regulation No.3 Year 2010 on quality standard of waste water in industrial area, in this case the outlet, shows that parameter of COD, pH, TSS, Selenium and Copper are appropriate to quality standard.